Violence and Human Prayer to God in Q 11 - Bazzana, Giovanni Battista (HTS teologiese studies, 2014)
The present article examines the use of κρούω in Q 11:9 against the backdrop of documentary papyri and Greek literary texts that employ the verb to evoke a stock scene of aggression and threat at the door of a house. In the unit 11:2–4, 9–13 the Sayings Gospel employs the same language and gestures in a similar rhetorical situation to advance a complex and ambiguous representation of human agency in prayer, which is not conceived as a mere passive expectancy of God’s intervention. This representation fits the socio-cultural profile of village scribes as the authors of Q, given their familiarity with administrative terminology and their acquaintance with widespread and simple rhetorical tropes. Moreover, such an ambiguous stance towards human agency is mirrored in Q’s similarly complex understanding of human participation in the establishment of God’s βασιλεία. Finally, comparable thematic and linguistic features have been detected in the ‘parable of the friend at midnight’ (Lk 11:5–8), strengthening the hypothesis that the parable might have been part of the Sayings Gospel.